2013
DOI: 10.1152/ajpendo.00639.2012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 11β-hydroxysteroid dehydrogenase-1 inhibition on hepatic glycogenolysis and gluconeogenesis

Abstract: The aim of this study was to determine the effect of prolonged 11␤-hydroxysteroid dehydrogenase-1 (11␤-HSD1) inhibition on basal and hormone-stimulated glucose metabolism in fasted conscious dogs. For 7 days prior to study, either an 11␤-HSD1 inhibitor (HSD1-I; n ϭ 6) or placebo (PBO; n ϭ 6) was administered. After the basal period, a 4-h metabolic challenge followed, where glucagon (3ϫ-basal), epinephrine (5ϫ-basal), and insulin (2ϫ-basal) concentrations were increased. Hepatic glucose fluxes did not differ b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 63 publications
2
6
1
Order By: Relevance
“…As noted above, previous studies have demonstrated that AMPK activation in the VMH is capable of generating a counterregulatory response to hypoglycemia (31,32). We have shown that increased hepatic glycogen content is associated with an increase in hepatic AMPK phosphorylation at the Thr172 site (35,36), an event that is most likely triggered by the enzyme becoming more susceptible to phosphorylation as a result of binding to intracellular glycogen (37). Future studies will be required to determine the event or events that trigger the afferent neural signal and the area or areas of the brain that coordinate altered hormone secretion.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…As noted above, previous studies have demonstrated that AMPK activation in the VMH is capable of generating a counterregulatory response to hypoglycemia (31,32). We have shown that increased hepatic glycogen content is associated with an increase in hepatic AMPK phosphorylation at the Thr172 site (35,36), an event that is most likely triggered by the enzyme becoming more susceptible to phosphorylation as a result of binding to intracellular glycogen (37). Future studies will be required to determine the event or events that trigger the afferent neural signal and the area or areas of the brain that coordinate altered hormone secretion.…”
Section: Discussionsupporting
confidence: 70%
“…Future studies will be required to determine the event or events that trigger the afferent neural signal and the area or areas of the brain that coordinate altered hormone secretion. To increase liver glycogen content, we infused fructose intraportally on the background of hyperglycemia and euinsulinemia as we have previously described (35,36,38). This was then followed by a 2-hour control period during which fructose was not infused and thereafter by a 2-hour hypoglycemic/hyperinsulinemic clamp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…animal models (9,33), and clinical studies using selective 11b-HSD1 inhibitors have now shown improvement in glycemic control in patients with type 2 diabetes mellitus, as well as reductions in BP and weight (10,11,34). However, in this study, 11b-HSD1 activity did not predict development of metabolic disease.…”
Section: European Journal Of Endocrinologycontrasting
confidence: 54%
“…Inevitably, some agents have off-target effects when used at high drug exposure in preclinical studies [83], but in our view this does not undermine the consistency of beneficial effects in preclinical studies of inhibitors with a variety of chemical structures. Both short-and long-term selective inhibition of 11βHSD1 in dogs decreases hepatic glucose production mainly by suppressing glycogenolysis [84,85]. Have these encouraging results translated to humans?…”
Section: βHsd1 Inhibitorsmentioning
confidence: 99%